1994
DOI: 10.1007/bf00003435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of unilateral ovariectomy on recruitment and growth of follicles in the rainbow trout, Oncorhynchus mykiss

Abstract: Virgin female rainbow trout, Oncorhynchus mykiss, were unilaterally ovariectomised at various stages of ovarian development to investigate the effect of the removal of one ovary on subsequent recruitment and growth of follicles in the remaining ovary. The right ovary was removed from groups of 12-15 fish, 12, 7 and 4 months before they were due to ovulate, and the gonadosomatic index and follicle number and size determined just prior to ovulation. There were no differences in fecundity or follicle size in fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 28 publications
(28 reference statements)
1
30
1
1
Order By: Relevance
“…Macroscopically, the response of European sea bass to ULO was similar to those previously reported for other fish species (Goswami & Sundaraj 1968a, Dadzie & Hyder 1976, Tyler et al 1994, 1996, 1997, Luckenbach et al 2008, i.e. the ovarian lobe remaining after surgery underwent a compensatory growth ultimately reaching a total mass equivalent to that of intact paired gonads.…”
Section: Morphological Responses To Ulosupporting
confidence: 84%
See 2 more Smart Citations
“…Macroscopically, the response of European sea bass to ULO was similar to those previously reported for other fish species (Goswami & Sundaraj 1968a, Dadzie & Hyder 1976, Tyler et al 1994, 1996, 1997, Luckenbach et al 2008, i.e. the ovarian lobe remaining after surgery underwent a compensatory growth ultimately reaching a total mass equivalent to that of intact paired gonads.…”
Section: Morphological Responses To Ulosupporting
confidence: 84%
“…Therefore, and unlike that reported for rainbow trout hemi-castrated at pre-or early vitellogenesis (Tyler et al 1994(Tyler et al , 1996(Tyler et al , 1997, the compensatory ovarian growth observed in European sea bass after ULO was not associated with recruitment of a complete new batch of primary oocytes into the secondary growth phase. Rather, such compensation was based on an extra recruitment of follicles at mid and late vitellogenesis, probably derived from the pool of early vitellogenic oocytes already existing in the ovary.…”
Section: Morphological Responses To Ulocontrasting
confidence: 71%
See 1 more Smart Citation
“…Il s'avérerait maintenant intéressant d'étudier les facteurs qui initient les processus de là croissance ovocytaire ainsi que ceux qui contrôlent le recrutement ovocytaire, surtout chez les poissons à pontes multiples qui divisent leur potentiel reproductif. La technique d'ovariectomie unilatérale, récemment développée (Tyler et al 1994), constitue un outil valable pour ce genre d'étude. D'autre part, l'étude des stéroïdes dits non classiques (Kime 1993) chez les poissons pourraient permettre une meilleure compréhension des mé-canismes contrôlant la régulation de l'ovogenèse.…”
Section: Resultsunclassified
“…The stages of ovarian development in fish were determined based on morphological characteristics and the size of the oocytes as described previously [15]. The five stages of ovarian development include: early pre-vitellogenesis (≤ 0.5 mm), late pre-vitellogenesis (≤ 0.65 mm), early-vitellogenesis (0.65-1.1 mm), med-vitellogenesis (1.1-2.1 mm) and latevitellogenesis (2.1-4.0 mm).…”
Section: Fish Sample Collectionmentioning
confidence: 99%